Food Security and Diet Diversity in Households from Morelos: La Nopalera - Villanueva Sánchez, Javier; Gallardo Medina , Delmy del Carmen; Ventura Zapata, Elsa; Solano Navarro, Araceli (Horizonte Sanitario, 2024)
Objective: To analyze the prevalence of food insecurity and the diet diversity from households in a highly marginalized locality.Materials and methods: Analytical observational study carried out in La Nopalera, Yautepec, Morelos. In a sample by-convenience selected households, with a structured survey, information was collected and analyzed to establish the association between the prevalence of food insecurity (FI) with the sociodemographic characteristics of the households and family food consumption at previous week. Parametric and non-parametric statistics at a significance level p